The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jcmm.14817
|View full text |Cite
|
Sign up to set email alerts
|

Dual TBK1/IKKɛ inhibitor amlexanox attenuates the severity of hepatotoxin‐induced liver fibrosis and biliary fibrosis in mice

Abstract: Although numerous studies have suggested that canonical IκB kinases (IKK) play a key role in the progression of liver fibrosis, the role of non-canonical IKKε and TANKbinding kinase 1 (TBK1) on the development and progression of liver fibrosis remains unclear. To demonstrate such issue, repeated injection of CCl 4 was used to induce hepatotoxin-mediated chronic liver injury and biliary fibrosis was induced by 0.1% diethoxycarbonyl-1, 4-dihydrocollidine diet feeding for 4 weeks. Mice were orally administered wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…These data suggested that TBK1 antagonist may modulate the immunosuppressive microenvironment by inhibiting the secretion of inflammatory cytokines in HCC cells and cancer-associated fibroblasts. Furthermore, consistent with the other study ( 61 ), our results showed the suppression of the activation of hepatic stellate cells and liver fibrosis by TBK1 antagonist ( Supplementary Figure 5C ). Due to the promoting effect of hepatic fibroinflammatory condition on the tumor immunosuppression ( 5 ), it is possible that the TBK1 antagonist attenuated the HCC immunosuppression by reducing the fibrosis and inflammatory environment of liver.…”
Section: Discussionsupporting
confidence: 93%
“…These data suggested that TBK1 antagonist may modulate the immunosuppressive microenvironment by inhibiting the secretion of inflammatory cytokines in HCC cells and cancer-associated fibroblasts. Furthermore, consistent with the other study ( 61 ), our results showed the suppression of the activation of hepatic stellate cells and liver fibrosis by TBK1 antagonist ( Supplementary Figure 5C ). Due to the promoting effect of hepatic fibroinflammatory condition on the tumor immunosuppression ( 5 ), it is possible that the TBK1 antagonist attenuated the HCC immunosuppression by reducing the fibrosis and inflammatory environment of liver.…”
Section: Discussionsupporting
confidence: 93%
“…Individually, AMLX and FSKN treatments promoted myocardial fibrosis resolution effectively compared to the placebo (in ICM+ PbT) ( Figures 3E–G ). Zhou et al had previously shown the anti-fibrotic potencies of AMLX treatment ( 28 ). Similarly, consistent with our findings, FSKN treatments were shown by El-Agroudy et al and Roberts et al to exert anti-fibrotic effects by inhibiting fibroblast activation, proliferation, and differentiation ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of liver fibrosis, mice were treated with a 0.1% diethoxycarbonyl-1,4-dihydrocollidine (DDC) diet for four consecutive weeks to establish a liver fibrosis model. The results showed that phosphorylated IKKε/TBK1 was increased in HSCs ( Zhou et al, 2020b ). After treatment with AM, mice with hepatobiliary fibrosis showed significantly improved liver function, lower serum AST, and ALT levels and reduced inflammation of liver Kupffer cells (KCs) ( Zhou et al, 2020b ).…”
Section: Ikkε In Pathological Statementioning
confidence: 99%
“…The results showed that phosphorylated IKKε/TBK1 was increased in HSCs ( Zhou et al, 2020b ). After treatment with AM, mice with hepatobiliary fibrosis showed significantly improved liver function, lower serum AST, and ALT levels and reduced inflammation of liver Kupffer cells (KCs) ( Zhou et al, 2020b ). During this process, AM inhibited the phosphorylation of IKKε/TBK1 in hepatic Kupffer cells, which may affect the phosphorylation of downstream STAT3.…”
Section: Ikkε In Pathological Statementioning
confidence: 99%
See 1 more Smart Citation